Intervensi Berbasis Kelompok: Sebuah Upaya Peningkatan Literasi Kesehatan Publik Terkait Depresi Maternal - Warnaini, Cut; Nurbaiti, Lina; Egitha WP, Luh; Rahmat, Dwi; Buana, Belva B; Rahim, Aulia R; Falah, Hidzul M; Agung, IDGN (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Background Maternal mental health during pregnancy and postpartum is a crucial factor impacting the well-being of both mother and baby. Maternal depression can occur during pregnancy (antenatal depression) or after delivery (postpartum depression). Antenatal depression can affect various aspects of maternal health, including nutritional status, which is a crucial factor in maintaining maternal health and fetal development. Furthermore, approximately 33% of women with postpartum depression have symptom onset during pregnancy, and 27% even before pregnancy. Health promotion through seminars or group-based interventions can significantly improve participants' knowledge levels over a period of time. Considering the importance of health promotion efforts as a preventative measure against maternal depression and the limited research evaluating knowledge retention of pregnant and postpartum mothers after group-based interventions such as health seminars, this study was conducted to assess maternal knowledge retention after two months of seminars on maternal depression. Methods The research design used in this study was a quasi-experimental design. Initial measurements were taken by assessing posttest 1 scores immediately after the seminar and compared with posttest 2 scores measured two months after the seminar. Results The decrease in posttest 2 scores compared to posttest 1 was less than 40% (p-value <0.05), indicating that a two-month period is still ideal for maintaining respondents' knowledge. Factors influencing the study's outcomes included respondents' age, education level, and gestational status. Conclusion Therefore, the seminar method is considered appropriate for increasing public literacy regarding maternal depression.